Diversity of Gastropod in Mangrove Ecosystems in Tomini Gulf - Mohamad Fahmi Kasim; Faizal Kasim; Sri Nuryatin Hamzah (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2019)
The purpose of this research is to know the diversity of gastropod in mangrove ecosystem of East Pohuwato Village, District of Marisa, Pohuwato Regency. This research was conducted in August to November 2015. The method used is a quadrant transect method measuring 1x1 meter. Data analysis includes calculation of diversity index and equality index. The results showed that 11 gastropods were found, namely Telescopium telescopium, Terrebralia palustris, Terrebralias ulcata and Cerithidea cingulata, Cerithium cobelti, Faunus ater, Littorina scabra, Noses planospira, Nasarius corodatus and Nasarius optimus, and Spinidrupa spinosa. The index value of diversity in the study sites ranged from 0.73-0.75 with the category of medium diversity. Epifauna Gastropod similarity index value between Station I and Station II is 70.59% while the similarity index value for gastropod type of treefauna between Station I and Station II is 60% and both are in the same category. In general this shows the similarity of species Epifauna and Treefauna on both Stations Keywords: gastropods; diversity; similarity; mangrove; ecosystem.